Natural selection and speciation in Atlantic cod and related cod-fish - Katrín Halldórsdóttir 1972- (2016)
Natural selection is the main force in evolution. Population genetics, the theoretical explanation of evolution in modern Darwinism, is a study of the frequencies and interaction of alleles and genes in populations and how they change under the influence of evolutionary forces. Population genomics extends the field to the whole genomes of the organisms. The fingerprints of natural selection can be detected in molecular data. The organismic models used for studying selection are of importance. The Atlantic cod, Gadus morhua, is well known for its extreme fecundity. Each female spawns millions of eggs each time. An organism with such a high fecundity should be able to withstand considerable selection and respond more quickly to environmental pressures than less fecund organisms. Therefore, Atlantic cod is an excellent model for studying natural selection at the molecular level in wild populations. There have been large improvements in molecular techniques and in methods of data generation in evolutionary biology in recent years which significantly enhance population genetics and genomics. Here in this thesis several of these methods are applied to study selection in Atlantic cod and related cod-fish species from the Atlantic and Pacific ocean. Candidate genes under selection were studied and the work was then extended to sequencing of whole genomes. Comparison between organisms of related taxa can be useful in estimating divergence and admixture and in understanding which selective factors are important in Darwinian fitness of the organisms. The cod-fish analysed are in addition to Atlantic cod, the Pacific cod, Gadus macrocephalus; Greenland cod, Gadus ogac; walleye pollock, Gadus chalcogrammus; Arctic cod, Boreogadus saida and Polar cod, Arctogadus glacialis. A study was done on structure and arrangement of candidate selected globin genes in the Atlantic cod genome. Balancing selection is one of the main forces in maintaining genetic variation in populations. Evidence of trans-species polymorphism, which is a ...